An Ethnographer’s Dilemma: Researching Birthing Practices in India (Medicine Anthropology Theory, 2022)
These field notes are based on my research study which aims to understand the recent changes and developments in childbirth practices in India that propagate natural birthing practices as a childbirth choice available to birthing women. Drawing from this multi-sited ethnographic study conducted in birth centres in India from November 2018 to October 2019, I reflect on my fieldwork engagements to show the dilemmas that emerged during my research. In these field notes, I examine my position as a researcher with a focus on the complex ways in which the relationship between the respondents (birth professionals and birthing couples) and the researcher is navigated in a field site.